Centralization vs. Decentralization: Measuring the Effectiveness of State Regulations in Accommodating the Potential of Community-Based Zakat and Waqf - Alisha Haviedzah; Uum Nur Umayah; Rafi' Karunia Putra; Qurrotul Ahsani Ma'rufah; Neng Isma Nur Holifah; Muhammad Khalid Albar; Muhammad Aidan Athallah Fath; Marwah Ayatillah P; Imroatur Rif'ah; Fernaldi Wafdan Zuhdi; Auliatun Dalalah; Amelda Nayla; Delfi Kusuma Nadia (Westscience Press, 2026)
Indonesia, as the country with the largest Muslim population in the world, has enormous potential for zakat and waqf to support the social welfare and economic development of the people. However, there is a significant gap between this potential and the realization of its collection and utilization. One factor influencing this condition is state policy, which tends to implement centralized zakat and waqf management through Law Number 23 of 2011 and Law Number 41 of 2004. This study aims to analyze the impact of this centralized policy on the sustainability of community-based zakat and waqf management organizations, and to assess the extent to which the state regulatory framework is able to optimize the potential of Islamic philanthropy without eroding social capital and public participation. The method used in this study is a conceptual approach through a literature review by examining various scientific sources, theories, and relevant Qur'anic and Hadith arguments. The results of the study indicate that although centralized policies provide benefits in terms of accountability and administrative standardization, these policies also have the potential to suppress the role of community-based philanthropic institutions due to bureaucratic burdens and rigid legal-formal structures. Therefore, this study recommends the implementation of an adaptive and inclusive hybrid governance model, which balances the formal legality of the state with the social legitimacy of the community to optimize the sustainable management of zakat and waqf in Indonesia. As an academic and policy implication, this study emphasizes that optimizing zakat and waqf cannot rely solely on legal approaches and administrative centralization but must also consider the sociological dimensions of Indonesian Muslim society, which are based on community and faith. By synergistically integrating the roles of the state and community, zakat and waqf governance is expected to increase institutional effectiveness while maintaining public participation, the core spirit of Islamic philanthropy